Skrining dan Bioaktivitas Ekstrak Buah Merah (Pandanus conoideus Lamk.) Asal Kabupaten Pegunungan Bintang terhadap Jamur Candida Albicans: Penelitian Randomisasi - Asrianto, Asrianto; Purwati, Rina; Setiani, Dwi; Asrori; Taufik Sahli, Indra; Hartati, Risda (Poltekkes Kemenkes Kendari, 2023)
The fungus Candida albicans is a pathogen that can infect the oral cavity, digestive tract, vagina, skin, and other body areas. Red fruit (Pandanus conoideus Lamk.) is one of the plants with several potential secondary metabolites as antimicrobials. This study aimed to determine the phytochemical content and the inhibitory ability of red fruit extract against the fungus C. albicans. This research is an experimental laboratory study using a completely randomized design. The red fruit was obtained from the Pegunungan Bintang. Sample preparation consisted of shelling, drying, and grinding. Extraction of secondary metabolites using the maceration-evaporation method. The red fruit oil extract was tested for phytochemical and inhibitory power. The sample extract concentration was dissolved using Tween 2%. Inhibition test using the Kirby-Bauer method. The results showed that the red fruit extract contained many secondary metabolites, including flavonoids, alkaloids, tannins, steroids, and triterpenoids. These compounds have pharmacological abilities. The methanol and ethyl acetate extracts of red fruit at 80% concentration only had diameters of 5.00 mm and 5.75 mm, respectively. The red fruit extract is not sensitive to C. albicans. This study concludes that red fruit has many secondary metabolites. The growth of the fungus C. albicans ATCC 10231 was not sensitive after being exposed to the red fruit extraction.